A Structural Equation Model of Self-Regulation and Healthy Habits as an Individual Protective Tool in the Context of Epidemics–Evidence From COVID-19 - Sousa, Sónia S.; Ferreira, Marisa M.; Cruz, Sara; Sampaio, Adriana; Silva-Fernandes, Anabela (Frontiers in Psychology, 2021)
Abstract Objective: The present study aims to explore the mediation role of self-regulation on health-related behaviors adoption or maintenance, mental health, and well-being during the COVID-19 confinement in a sample of adults in Portugal. Design: One-hundred fifty individuals (118 females, 32 males; Mage = 33.57 y; SD = 12.71) filled an online survey to assess self-regulation, healthy behaviors, mental health, and well-being perception, during the early months of the pandemic (June-August, 2020). Main Outcome Measures: Self-regulation capacity, adoption or maintenance of healthy habits, mental health -including stress management, and the perception of one’s well-being were evaluated using a structural equation model (SEM). Results: Self-regulation had direct effects on healthy habits and mental health and indirect effects on well-being and mental health mediated by healthy habits. In specific, a positive direct effect on healthy habits (β = .497, p < .001) and a negative direct effect on mental health (β = -.428, p < .001); and a positive indirect effect on well-being perception, mediated by healthy behaviors and mental health (β = .253, p = .003), and a negative indirect effect on mental health, mediated by healthy habits (β = -.208, p = .003). Additionally, healthy habits exerted direct effects on well-being perception and mental health. A positive direct effect on well-being perception (β = .254, p = .012), and a negative direct effect on mental health (β = -.418, p < .001) were further observed. No direct effect of mental health was observed in well-being perception (β = -.199, p = .068). Finally, a negative correlation was observed between self-regulation and weeks of confinement (r = -.208, p = .021). Conclusions: Self-regulation seems to be a good indicator of adopting a healthy lifestyle and better mental health and well-being in the context of the COVID-19 pandemic. Future preventive actions and interventions to build long-term global preparedness for future health emergencies, such as COVID-19, should explore the importance of self-regulation as an important individual and collective protective factor.